Revitalizing Student Entrepreneurship Interest: Integrating Entrepreneurship Education, Campus Environment, and Creativity - Fernando Saragih; Emilia Gie; Gallex Simbolon (Universitas Negeri Padang, 2025)
Indonesia is endowed with abundant natural resources, including those in Malaka Regency, East Nusa Tenggara. However, these resources have not been fully utilized to stimulate entrepreneurial growth, as reflected in the low entrepreneurial interest among students. This study examines the influence of the campus environment, entrepreneurship education, and creativity on students’ entrepreneurial interest. A quantitative survey method was employed with a sample of 84 students from Malaka Regency, selected through non-probability incidental sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The results indicate that, collectively, the campus environment, entrepreneurship education, and creativity significantly influence entrepreneurial interest, contributing 52%. Individually, creativity has a positive and significant effect, whereas the campus environment and entrepreneurship education do not show statistically significant effects. These findings underscore creativity as the most dominant factor in fostering entrepreneurial interest, while the campus environment and entrepreneurship education require further strengthening to become more effective.